Linguistic sexism in Qatari Primary Mathematics textbooks - Mohamad Subakir Mohd Yasin; Bahiyah Abdul Hamid; Yuen, Chee Keong; Zarina Othman; Azhar Jaludin (Penerbit UKM, 2012)
Linguistic sexism and gender stereotyping are barriers to gender equality. If they are inculcated at an early age, they could be institutionalized and become part of the social code. Hence the school environment, where children receive their earliest education about society, norms, culture and the world around them, should be free of such biasness.One medium where linguistic sexism and gender stereotyping can exist is school textbooks. Children exposed to textbooks that contain gender ideology may internalize it.This paper, therefore, aims to study the linguistic sexism in Qatari primary mathematics textbooks. A quantitative qualitative approach is adopted. Wordsmith Tools 5.0 is used for the quantitative analysis and Fairclough’s (1989) Critical Discourse Analysis (CDA) is used for the qualitative analysis. The findings reveal that males are more visible than females in imported texts. However, in the Qatari published textbooks, females are more visible and dominant than males. This paper also discusses the implications of the findings on teaching and learning in the schools. Its objective is to raise the awareness of the existence of linguistic sexism and gender stereotyping in school textbooks.